Correlation of Respiratory Physiologic Parameters in Mechanically Ventilated Coronavirus Disease 2019 Patients - Saha, Biplab K. (Crit Care Explor, 2021)
Acute respiratory distress syndrome secondary to severe acute respiratory syndrome coronavirus-2 pneumonia or coronavirus disease 2019-related acute respiratory distress syndrome is the primary cause of mortality in coronavirus disease 2019. Some studies have described the concept of “high and low” elastance coronavirus disease 2019-related acute respiratory distress syndrome and proposed individualized management for the acute respiratory distress syndrome, deviating from low tidal volume ventilation. We report simultaneously measured respiratory parameters (static lung compliance, alveolar dead space ventilation, and shunt fraction) in 14 patients with advanced coronavirus disease 2019-related acute respiratory distress syndrome. The results were consistent with typical acute respiratory distress syndrome and did not support the concept of high-type coronavirus disease 2019-related acute respiratory distress syndrome and low-type coronavirus disease 2019-related acute respiratory distress syndrome.